Analisis Nilai-Nilai Pancasila yang Terkandung dalam Tradisi Pernikahan Masyarakat Melayu di Desa Mensere, Kecamatan Tebas, Kabupaten Sambas - Putra, Dede Yas; Syamsuri, Syamsuri; Purnama, Shilmy; Imran, Imran; Atmaja, Thomy Sastra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe the Pancasila values ​​contained in the wedding traditions of the Malay community in Mensere Village, Tebas District, Sambas Regency. A qualitative approach with descriptive methods was used in this research. The subjects in this research were village heads, traditional leaders and religious leaders. The data collection used was interviews, observation, and documentation using the Miles and Hubberman model data analysis technique which consists of data reduction, data presentation, and drawing conclusions. The results of this research show that the wedding procession in the Malay wedding tradition consists of three stages of the procession, namely pre-wedding, wedding and post-wedding. The values ​​of Pancasila are contained in the marriage traditions of the Malay community, the values ​​of divinity, humanity, unity, deliberation and justice. And these functions and meanings are divine values ​​indicating the spiritual and religious aspects of marriage, human values ​​which emphasize social care and tolerance, unity values ​​which strengthen family relationships and involve community mutual cooperation, deliberation values ​​where decisions regarding marriage are taken by deliberation to reach consensus, and justice values ​​which in the Malay marriage tradition exist social equality without distinguishing between the economic status of the community